Wedding Photography Online Booking System (WePOBS) / Anis Ruhana A S Azman - A S Azman, Anis Ruhana (2017)
At the moment, the reservation management at AD6 Photography still operating manually. All of the reservation records still being kept in the log book. There are limitations in storing all the booking information in files physically such as the record were exposed to missed customer’s call, data redundancy, and the vulnerability of the log book. Therefore, Wedding Photography Online Booking System (WePOBS) is developed in order to control and manage booking information. WePOBS can allow customers to make online booking and also manage their booking detail by their own. Besides that, this system can reduce the time taken in doing booking process and it will become more ef-ficiently to manage all the prototyping of booking process. AD6 company is focusing on wedding event only. Waterfall model is used as a methodology in developing WePOBS. This methodology consists six phases which are analysis phase, design phase, development phase, testing phase, implementation phase, and maintenance phase. After the implementation of WePOBS is completed, system evaluation is conducted regarding questionnaires given to 30 re-spondents and three experts. The evaluators evaluate six criteria of system which are usability, satisfaction, consistency, user interface, convenience, and customer relation-ship management. Based on respondent analysis, showed that the highest mean was 4.47 (SD = 0.507) for consistency section of the system. It can be concluded that the WePOBS gave more benefits for users and hopefully it will contribute further by evolving to a better booking management system.